The Nexus among Green Financing: Companies in G20 Emerging Market Countries - Imamah, Nur; Trinugroho, Irwan; Arifin, Layyin Nafisa; Fahri, Luki Okta (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2025)
Research Originality: This study addresses this urgent research gap by examining not only these relationships but also the underexplored role of national R&D capacity as a moderating factor, highlighting how emerging economies' innovation limitations may dilute the benefits of green capital inflows. Research Objectives: This study analyzed the impact of green financing and FDI on firm profitability and productivity in G20 emerging markets, and assess how R&D expenditure moderates these effects. Research Method: Panel data from 57 multinational companies across ten G20 emerging market countries during 2016–2021 were analyzed using fixed-effect regression. Empirical Results: Green financing and FDI both show significant positive impacts on firm profitability and productivity. However, R&D negatively moderates the green finance–profitability link and has no significant moderating effect on productivity or the FDI relationship, suggesting structural inefficiencies in R&D systems within emerging economies. Implications: The findings call for urgent policy interventions to enhance R&D infrastructure and efficiency in G20 emerging markets. Redirecting subsidies from fossil fuels to green innovation, fostering public-private R&D collaboration, and strengthening institutional frameworks can help unlock the full potential of green finance and FDI in supporting a sustainable economic transformation. JEL Classification: Q5, G3, F2